TRANSFORMATION OF CHURCH-BASED BUSINESS GROUP MANAGEMENT TO REALIZE INDEPENDENT, PRODUCTIVE, AND COMPETITIVE CONGREGATIONS AT HKBP PARIK SABUNGAN - Nana Triapnita Nainggolan; Ester Mawar Siagian; Delviana Romauli Wanti Sihombing; Benyamin Nababan (RADJA PUBLIKA, 2026)
Women play a crucial role in the household economy, but the majority still face obstacles to limited access to technology, low financial literacy, weak business governance, and lack of product innovation. The Community Service Program (PKM) aims to overcome these problems. Economic empowerment is one of the important strategies in improving the welfare of the community, including the church community. The church not only serves as a center for spiritual formation, but also has a strategic role in developing the economic capacity of the congregation through the formation of professionally managed business groups. This Community Service (PkM) activity aims to increase the congregation's understanding of effective business group governance so that it is able to create sustainable economic independence. The methods used include counseling, interactive discussions, case studies, and assistance in preparing business plans. The results of the activity showed an increase in participants' understanding of business governance principles, business group organizational structure, financial recording system, and business development strategies. This program is expected to be the foundation in building church business groups that are transparent, accountable, productive, and able to improve the welfare of the congregation.